Chechens in Germany : the conflict between integration and assimilation - Malinowski, Igor (2021)
;Islamists, terrorists, bandits. Chechens worldwide are associated with their very negative reputation. But very little is known about this small ethnic group whose culture has a long ancient history. As long as their cultural heritage goes back, their war-torn history is also an elementary part of their identity. Since round about 400 years there have been various armed conflicts and wars between Russia and Chechnya. After the collapse of Soviet Union in 1991 Chechnya declared itself as the independent state “Chechen Republic Of Ichkeria”. This resulted in two Chechen wars, the first one endured from 1994-1996 with the Chechens defeating the Russian troops. The second Chechen war took place between 1999 and 2009 and was declared as an anti-terror campaign. Afterwards a pro-Russian government has been established with Ramzan Kadyrov1 who is frequently accused by NGOs, journalists and human rights activists of massive human right abuses, arbitrariness, corruption and an exaggerated personal cult. Reasons for more than 300.000 refugees living in Europe coming along the last 25 years. Diverse studies have been developed to understand the political situation between Chechnya and Russia, but barely any studies deal with the new living conditions in the countries of their new residence, nor how their integration works in combination with their Adats (characteristic way of living/honor code). Through this research I am giving an overview of Chechen behavior rules called Adat, what difficulties they face between integrating in order to start a new life and maintaining their own identity, which has been exposed to repression, war and the fight for surviving for the last four centuries. But also how the actual “Being Chechen Like” identity changes along the process of integration far away from their homeland.